A Liquid-Level Sensing Technique Based on Differential Detection of Correlation Peaks From Broadband Chaos - Heng Yi; Li Xia; Jun Xu; Can Yu; Ying Wu; Chen Li; Lin Zhu (IEEE Photonics Journal, 2017)
A highly sensitive liquid-level sensing technique is proposed and experimentally demonstrated. Two narrowband fiber Bragg gratings (FBGs) with high reflectivity are used to filter out the two light signals from the broadband chaos. Two weak FBGs are served respectively as the liquid-level sensors at two different sensing points. The change of liquid-level will induce the wavelength shift of the weak FBGs, which can be demodulated through calculating the amplitude difference in the logarithm of two cascaded correlation peaks in the cross-correlation spectrum. Adopting the differential calculation of the cascaded correlation peak amplitudes can avoid the complex wavelength detection and enhance the robustness against the power variation of the broadband chaos. Our method can also support the simultaneous multiplexing and locating with high resolution from the time delays of the corresponding correlation peaks. Experimental results show that the liquid level changes linearly with the relative peak amplitude difference in the logarithm and the sensitivity is around 0.019/mm. The sensing resolution of liquid-level can reach at least 3 mm, and the relative resolution is around 0.055. Moreover, the real-time fiber fault monitoring can be achieved with a spatial resolution of around 2.8 cm, which improves the survivability in harsh environment.